Copresence is a Problematic Resource for Leisure Mobility: One Hub, Multiple Passenger Experiences on a Sunday Evening Return Trip - Baron, Nacima; Hasan, Ali (Téoros, 2020)
This paper analyzes copresence patterns among travellers in a suburban station. The authors investigate how tourists and other travellers experience physically and socially the spaces of public transport. In a first part, a field study is introduced after a multidisciplinary theoretical background (sociology, geography, ethnology of stations). It helps selecting the best moment to develop the methodology, that is, the moment in which the diversity of users and behaviours is maximized. In a second part, two field results are presented: first, Sunday afternoon as being the best moment to observe copresence, and second, the configuration of social interaction as obeying a dualistic structure. A third part questions the opposition between the experience of copresence as being a polite and distant coexistence among some users and a much warmer interaction among others. The explanation for such a divide lays first in the unequal mobility skills tourists and non-tourists may mobilize and, second, this opposition seems connected to the construction of a mobile community identity in the long term.